Formulation of self-nano emulsifying drug delivery system (SNEDDS) Red Ginger extract (Zingiber Officinale var. rubrum) - Erliyana, Mila; Widyaningsih, Wahyu; Wumu, Dea Anggrainy; Wulansari, Widyanari Febriyana (Media Farmasi: Jurnal Ilmu Farmasi, 2022)
Red ginger extract is one of the new medicinal discoveries made from natural substances that has pharmacological benefits in the treatment of diabetes. Many gingerol components in red ginger can aid in the treatment of diabetes mellitus. However, the administration of red ginger extract is not so effective, a delivery system such as SNEDDS (Self-Nano Emulsifying Drug Delivery System) must be developed. When compared to standard formulations, SNEDDS can boost the oral bioavailability of lipophilic medicines by up to 2.4 times. The oil phase of SNEDDS red ginger extract was virgin coconut oil, with tween 80 as a surfactant and PEG 400 as a co-surfactant. The fourth formula of the SNEDSS preparation of red ginger rhizome extract satisfied the requirements for a good nanoemulsion particle size in this study, with a percent T value of 99.7% and PSA test data showing that this formulation met the requirements for a good nanoemulsion particle size